KOMPOSISI DAN STRUKTUR RERUMPUTAN DI KAWASAN DANAU TOBA DESA HARANGGAOL KECAMATAN HARANGGAOL HORISON KABUPATEN SIMALUNGUN SUMATERA UTARA - Novia Wulandari Tarigan; M Zaidun Sofyan; Nursahara Pasaribu (Saintia Biologi, 2013)
The composition and structure of Grasses in Haranggaol Village Haranggaol Horison Subdistrict Simalungun Regency North Sumatra has been studied from April to July 2012. The objective of the study was to determine the composition and structure of grasses at different altitudes. Sampling area was defined by purposive sampling method  and divided into three locations based on altitude with 20 plots of 1 x 1 m size for each area. From the study it was found 24 species of grasses that belong to two families. The first location was dominated by Microstegium ciliatum (81.095%), the second was dominated by Deyeuxia brachyathera (68.504%) and the third was dominated by Leersia hexandra (79.158%). The diversity index  (H')  of grasses are 1.557, 1.790 and 1.414 in the location I, II and III, respectively and equitability index (E) of grasses are 0.607, 0.661, 0.726 in the location I, II and III, respectively. The similarity index ranges from 30 to 50%, with the highest similarity index is 50% that was found between location I and II.   Keyword: composition, grass, Haranggaol, structure